2019
DOI: 10.1016/j.ypmed.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life events are associated with perinatal cigarette smoking

Abstract: Perinatal smoking, including smoking during pregnancy and postpartum smoking relapse, is a persistent public health problem. While childhood trauma has been linked to perinatal smoking, less is known about the association with more proximal stressful life events (SLEs). The objective of this study was to examine the association between SLEs that occurred during the year prior to childbirth with perinatal smoking. Using the Pregnancy Risk Assessment Monitoring System 2009–2011, perinatal smoking was assessed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
4
20
1
1
Order By: Relevance
“…Overall, these observations indicate that SLEs experienced in the year prior to childbirth are associated with perinatal cannabis use, perhaps especially pre‐pregnancy cannabis use and, less so, use during pregnancy. This observation is similar to our prior publication examining the link between SLEs and cigarette smoking during the perinatal period .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, these observations indicate that SLEs experienced in the year prior to childbirth are associated with perinatal cannabis use, perhaps especially pre‐pregnancy cannabis use and, less so, use during pregnancy. This observation is similar to our prior publication examining the link between SLEs and cigarette smoking during the perinatal period .…”
Section: Discussionsupporting
confidence: 91%
“…Less is known about the more proximal SLEs. We recently reported that SLEs in the year prior to childbirth were associated with increased odds of perinatal cigarette smoking, especially cigarette smoking during pregnancy . Those who reported cannabis use during pregnancy had a greater number of SLEs in the year prior to childbirth in 2009–11 ; however, this research was limited to three states (Alaska, Hawaii, Vermont) and did not examine the relationship between SLEs and cessation of cannabis during pregnancy nor with postpartum cannabis relapse.…”
Section: Introductionmentioning
confidence: 97%
“…Demographic characteristics included sex (male vs. female), age (23-35 vs. 36-42 years), living with a partner (yes vs. no), parental status (no children, a child aged ≤ one year and have a child aged >one year, half of women who obtain smoking cessation during pregnancy relapse in the first year postpartum) (Allen et al, 2019;Rockhill et al, 2016) which were assessed in 2015, adverse life events in the preceding 12 months (for example: separation from the spouse or death of a close person; yes vs. no), the experience of physical violence in the preceding 12 months (yes vs. no) and the experience of psychological violence in the preceding 12 months (yes vs. no) which were assessed in 2011.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…1 Indeed, exposure to stressful life events and perceived stress prior to or following a quit attempt are linked with relapse. 2,3 In human laboratory studies, acute stress challenges after varying lengths of abstinence lead to increases in cigarette cravings, smoking frequency and intensity. 4,5 Despite the observed links between stress and smoking behavior, these studies pose many challenges.…”
Section: Introductionmentioning
confidence: 99%